CBDC in the market for payments at the point of sale: Equilibrium impact and incumbent responses - Walter Engert; Oleksandr Shcherbakov; André Stenzel (Bank of Canada, 2024)
We investigate the introduction of a central bank digital currency (CBDC) into the market for payments. Focusing on the point of sale, we develop and estimate a structural model of consumer adoption, merchant acceptance and usage decisions. We counterfactually simulate the introduction of a CBDC, considering a version with debit-like characteristics and one encompassing the best of cash and debit, and characterize outcomes for a range of potential adoption frictions. We show that, in the absence of adoption frictions, CBDC has the potential for material consumer adoption and merchant acceptance, along with moderate usage at the point of sale. However, modest adoption frictions substantially reduce outcomes along all three dimensions. Incumbent responses required to restore pre-CBDC market shares are moderate to small and further reduce the market penetration of CBDC. Overall, this implies that an introduction of CBDC into the market for payments is by no means guaranteed to be successful.
Keywords: C51; D12; E42; L14; L52; 330; Bank notes; Digital currencies and fintech; Econometric and statistical methods; Financial services